Analisis Distingsi di Era Digital Society 5.0 Antara Local Preneur, Local Fleuncer & Local Pride pada Local Product Tanaman Purun Kalimantan Tengah - Ida Bagus Suryanatha; Selvia, Fitriana; Kaharap, Yorgen; Ayu, Katriani Puspita (Jurnal Administrasi Politik dan Sosial, 2024)
This study aims to examine and analyze the distinction that occurs among Local Preneur, Local Fluencer in Local Pride branding based on Local Wisdom. Qualitative research method with a case study approach. The findings of this study are that there is a distinction in local purun products where in terms of quality and price they are still unable to reach non-local goods. In addition, not many local influencers are aware of the local brands produced by local entrepreneurs so that local pride in Central Kalimantan has not been stimulated massively.